Silibinin inhibits accumulation of myeloid‐derived suppressor cells and tumor growth of murine breast cancer. (20th January 2014) - Forghani, Parvin; Khorramizadeh, Mohammad R.; Waller, Edmund K.
Abstract Myeloid‐derived suppressor cells (MDSC)s increase in blood and accumulate in the tumor microenvironment of tumor‐bearing animals, contributing to immune suppression in cancer. Silibinin, a natural flavonoid from the seeds of milk thistle, has been developed as an anti‐inflammatory agent and supportive care agent to reduce the toxicity of cancer chemotherapy. The goals of this study were to evaluate the effect of silibinin on MDSCs in tumor‐bearing mice and antitumor activity of silibinin in a mouse model of breast cancer. 4T1 luciferase‐transfected mammary carcinoma cells were injected into in the mammary fat pad female BALB/c mice, and female CB17‐Prkdc Scid/J mice. Silibinin treatment started on day 4 or day 14 after tumor inoculation continued every other day. Tumor growth was monitored by bioluminescent imaging (BLI) measuring total photon flux. Flow cytometry measured total leukocytes, CD11b+ Gr‐1+ MDSC, and T cells in the blood and tumors of tumor‐bearing mice. The effects of silibinin on 4T1 cell viability in vitro were measured by BLI. Treatment with silibinin increased overall survival in mice harboring tumors derived from the 4T1‐luciferase breast cancer cell line, and reduced tumor volumes and numbers of CD11b+Gr‐1+ MDSCs in the blood and tumor, and increased the content of T cells in the tumor microenvironment. Silibinin failed to inhibit tumor growth in immunocompromised severe combined immunodeficiency mice, supporting the hypothesis that anticancer effect of silibinin is immune‐mediated. The antitumor activity of silibinin requires an intact host immune system and is associated with decreased accumulation of blood and tumor‐associated MDSCs.